2010
DOI: 10.1111/j.1471-0528.2010.02540.x
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal interventions for overweight or obese pregnant women: a systematic review of randomised trials

Abstract: Background Overweight and obesity during pregnancy is an increasing health problem.Objective A systematic review to assess the benefits and harms of antenatal dietary or lifestyle interventions for pregnant women who are overweight or obese.Search strategy The Cochrane Controlled Trials Register (CENTRAL) was searched (last search January 2010). Reference lists of retrieved studies were searched by hand. No date or language restrictions were used.Selection criteria Randomised controlled trials comparing antena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
204
0
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(213 citation statements)
references
References 46 publications
4
204
0
5
Order By: Relevance
“…Most studies have assessed changes in weight gain throughout pregnancy, not change in subcutaneous fat. In a review of the literature on weight gain in pregnancy, Dodd (2010) was unable to demonstrate any statistical difference in perinatal outcomes when weight gain was restricted. 40 We have shown a correlation between BMI and SFT2, consistent with a previous report.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies have assessed changes in weight gain throughout pregnancy, not change in subcutaneous fat. In a review of the literature on weight gain in pregnancy, Dodd (2010) was unable to demonstrate any statistical difference in perinatal outcomes when weight gain was restricted. 40 We have shown a correlation between BMI and SFT2, consistent with a previous report.…”
Section: Discussionmentioning
confidence: 99%
“…In a review of the literature on weight gain in pregnancy, Dodd (2010) was unable to demonstrate any statistical difference in perinatal outcomes when weight gain was restricted. 40 We have shown a correlation between BMI and SFT2, consistent with a previous report. 29 Our research has also demonstrated that there is a wide variation in SFT1 and SFT2 for any given BMI in the overweight/obese categories ( Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…In women with a BMI > 40 kg/m 2 (very severely obese), for whom pregnancy risks are incrementally greater (CMACE/RCOG, 2010), limiting gestational weight gain may reduce the risk of adverse pregnancy outcomes (Crane et al, 2009). A number of randomised-controlled trials have sought to examine the efficacy of pregnancy intervention approaches such as diet and exercise programmes, cognitive behavioural therapy (CBT), and social (cognitive) learning theory, on maternal weight gain and fetal growth (Dodd et al, 2010;Smith and Lavender 2011;Thangaratinam et al, 2012). However, recent RCTs of behaviour change interventions have experienced low uptake (Dodd et al, 2014;Poston et al, 2015), indicating poor acceptability.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent RCTs of behaviour change interventions have experienced low uptake (Dodd et al, 2014;Poston et al, 2015), indicating poor acceptability. Multiple systematic reviews (Dodd et al, 2010;Campbell et al, 2011) and meta-analyses (Oteng-Ntim et al, 2012;Agha et al, 2014) have concluded that behaviour change interventions to date which have focused on limiting GWG via a combination of dietary counselling, weight monitoring, and exercise programmes for all categories of women with a BMI > 30 kg/m 2 have had moderate to no influence on GWG, and no effect on other perinatal outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…pre-eclampsia, gestational diabetes, caesarean section, fetal macrosomia and/or offspring obesity) consequences of obesity? Many trials use limitation of maternal weight gain during pregnancy as their primary outcome (11) . Maternal obesity is a significant determinant of gestational weight gain, which if excessive is an independent predictor of adverse maternal and fetal outcome for pregnancy, with consequent lifelong health implications.…”
Section: Overview Of Interventionsmentioning
confidence: 99%